Análises microbiológicas e quantificação de proteína de soja pela metodologia isotópica (δ13C and δ15N) em hambúrgueres bovinos de marcas comerciais brasileiras - Ducatti, Rhani [UNESP] (2014)
The burger is a manufactured meat product and potential vehicle of bacteria producers or not of toxins in various stages of processing, from its origin to the stage of transformation, storage, transport and distribution to consumption. Moreover, their composition requirements are susceptible to fraud by excessive use of protein extenders. These ingredients help in reducing the cost of formulation of the final products and maximize profits of fraudulent industries. The supervisory agencies monitoring is hindered by the lack of appropriate analytical methodologies. Within this context, it is necessary to evaluate the hygienic- sanitary aspects of burgers through microbiological analysis and the determination and quantification of soy protein. Were analyzed 110 samples of beef hamburgers of 11 brazilian trademarks by the technique of stable isotopes of Nitrogen-15 and Carbon -13 and second microbiological methodology described by Normative Instruction n° 62 of August 26, 2003. All 11 brazilian trademarks presented bacterial counts within the limit (5x103 CFU/g) for coliforms at 45°C , while the values for Staphylococcus coagulase positive were above the allowed patterns (5x103 CFU/g) in brands H (samples 1 and 7). Brands B (sample 5) , D (sample 5) , E (sample 5) and G (sample 4) also had scores above the stipulated (3x103 CFU/g) for Clostridium sulphite reducing to 46°C and sample 6 of brand L was positive for Salmonella spp. Only 3 samples of G brand were within 4% addition of non-meat protein stipulated by IN 20 07/31/2000. All other 107 samples from 11 trademarks cheated the specific legislation